Pharmacy administration, leadership, and management - Bautista, Learni Magdalena A.; Tubon, Nelson T.; Cera, Eugene Marc D. III (Quezon City : C & E Publishing Inc., 2019)
We designed the first edition of Pharmacy Administration, Leadership, and Management appropriate to the Philippine setting. It is supplemented with worksheets that address the needs of pharmacy students and pharmacist to successfully overcome the challenges in all practice settings in the field of pharmacy. It also serves as an ultimate learning guide and an introduction for students who are interested in this rapidly expanding field of pharmacy practice. This textbook is outlined and organized to reflect the basic operational and supervisory functions performed by a pharmacy manager. It is divided into three parts and is further divided into chapter that discuss in detail the aspects or components of management.
Pharmacy's cadence : drumbeat of a profession -- Development of pharmacy in history as a healing profession -- Pharmacy reborn : pharmaceutical care and medication -- Therapy management -- Communications in pharmacy practice -- Ethics in pharmacy practice -- Career planning : practice areas in pharmacy -- Governmental and voluntary oversight of pharmacy -- Pharmacy associations -- Using the pharmacy literature and writing for it -- Postgraduate educational opportunities -- Current issues in pharmacy.
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL SERVICES -- ORGANIZATION AND ADMINISTRATION; PHARMACY -- ORGANIZATION AND ADMINISTRATION